Prevalence, clinical pattern and immediate outcomes of HIV-infected children admitted to Al Sabah Children's Hospital, South Sudan - Gawar Gel (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2019)
Introduction: HIV continues to be a major global health issue. There were approximately 2.1 million infected children aged <15 years in 2017 and most were in sub-Saharan Africa. South Sudan with its low prevention of mother to child transmission (PMTCT) coverage has a greater risk of high transmission rates of HIV from mothers to their children. Objective: To determine the prevalence of HIV infection, the clinical pattern, and the immediate outcomes of children admitted to Al Sabah Children's Hospital. Method: This was a cross-sectional descriptive study, with a longitudinal component for the immediate outcome. A total of 828 children were recruited: 424 aged <18 months and 424 aged ≥ 18 months. HIV rapid tests were done to confirm the HIV infection for children aged ≥ 18 months, while HIV DNA-PCR was done to confirm the HIV infection for children aged <18 months found to be HIV exposed. Results: Twenty four children tested HIV positive giving an overall HIV prevalence of 2.8% (95% CI 1.8 - 4.2). The clinical characteristics associated with HIV infection were: a history of cough (p=0.001), weight loss (p <0.001), oral thrush (p <0.001), lymphadenopathy (p= 0.001), ear discharge (p<0.001), skin lesion (p <0.001), hepatomegaly (p <0.001), and splenomegaly (p <0.01). Factors associated with prolonged hospital stay were history of weight loss (OR=4.96, 95% CI 2.68-9.18), skin lesions (OR=3.60, 95% CI 1.36-9.56), and weight for height/length z score<-3SD (OR=8.67, 95% CI 4.70-15.99). Conclusion: The prevalence of HIV among this hospital-based population of children aged less than 15 years was 2.8%. Children who presented with cough, weight loss, oral thrush, lymphadenopathy, ear discharge, skin lesion, hepatomegaly, and splenomegaly in this setting were likely to have HIV infection and should, therefore, raise suspicion for testing and early diagnosis.